Philippine social history : global trade and local transformation - McCoy, Alfred W.;De Jesus, Ed. C. (Quezon City, Philippines : Ateneo De Manila University Press, 1982)
With the publication of this volume, the Filipinists have at last entered the debate. The Philippines experienced one of the most intensely documented transitions to modernity of any Third world nation.
Preface -- Luzon -- Visayas -- Mindanao -- Conclusions.
Includes bibliographical references and index.
Keywords: HISTORY -- PHILIPPINES